Certain Results on Hypergeometric Series for Meijer’s G-Functions - Sharma, Basanta Raj (Nepal Journal of Science and Technology, 2010)
This paper has deal with certain aspects in the development of hypergeometric series, which are the most significant topics of special function. Moreover, making use of the known results, Meijer's G-functions of hypergeometric type have also been generalized by increasing the number of variables in terms of double Barnes' type of contour integrals. Key words: hypergeometric series, Meijer's G-function, q-series, the pFq-series, when p>q+1, Mellin-Barnes' type, double summation DOI: 10.3126/njst.v9i0.3186 Nepal Journal of Science and Technology 9 (2008) 187-193